AN EXPLORATIVE STUDY ON THE IMPLEMENTATION OF PROBLEM-BASED LEARNING (PBL) IN TEACHING READING - Burhan Fathurrohman; Dian Adiarti; Tuti Purwati (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2021)
This research explores the implementation of problem-based learning (PBL), aspects of PBL, and teacher’s and students’ perceptions about PBL. This research was conducted at SMA Negeri 2 Cilacap, taking 34 tenth grade students as the sample from X IPS 1 and an English teacher as a participant. The data were collected using observation, questionnaires, and interviews. The data were analysed using Miles and Huberman’s (1984) four types of analytical activity and presented descriptively. The result shows that the implementation of PBL in on the chosen sample is in line with the stages of PBL implementation entailing: 1) the teacher organizes the students to a problem, 2) the teacher organizes the students to learn, 3) the teacher as the participant helps the independent inquiry and groups, 4) the teacher helps the students develop and present the work, and 5) the teacher analyses and evaluates the problem-solving process. Then, the analysis of the aspects of PBL suggests such things as 1) the problem as the point in PBL, 2) the students’ discussion activities, 3) the teacher’s help in students’ discussion, 4) the students’ activeness, and 5) the teacher’s and students’ perception about PBL in reading skill. The teacher positively thinks that the materials in reading skills match with the PBL teaching model. It was found that PBL leads the students to discuss and train their activeness, ability to learn to solve problems, share ideas, and work cooperatively in a group. Another finding also denotes that they think that PBL is one interesting model which can support them to understand the text, because students can get insight from their friends and their teacher when having discussion.